Mesomorphic, morphologic and thermotropic properties of 4-hexyl-N-(4-hexadecyloxysalicylidene) aniline - Nesrullajev, A; Bilgin-Eran, B (ELSEVIER SCIENCE SA, 2005)
The mesomorphic, morphologic and thermotropic properties of the liquid crystalline material 4-hexyl-N-(4-hexadecyloxysalicylidene)aniline (1) have been investigated. Investigations on the peculiarities of heterophase regions during phase transitions between smectic C mesophase and isotropic liquid have been carried out. Hysteresis in the temperature width of the heterophase regions, temperatures of the phase transitions between smectic C and isotropic liquid, and smectic C and solid crystal and also the hysteresis in the temperature width of the smectic C mesophase in the salicylaldimine compound I have been found. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: mesomorphic properties; morphologic properties; thermotropic properties; TETRANUCLEAR PLATINUM MESOGENS; LYOTROPIC NEMATIC MESOPHASES; PHASE-TRANSITIONS; LIQUID-CRYSTALS; PECULIARITIES; Materials Science